Tuning the metal loading of Pt/CeO2 catalysts for the water-gas shift reaction - Clément Molinet-Chinaglia; Luis Cardenas; Philippe Vernoux; Laurent Piccolo; Stéphane Loridant (Materials Today Catalysis, 2024)
Identifying active platinum species at the surface of Pt/CeO2 catalysts is still a hot topic in the literature. In this work, an oxidizing pretreatment at 500 °C was applied to generate ultradispersed PtOx species before the reaction. It is shown that the molar activity of such catalysts for the water-gas shift reaction is strongly dependent on the platinum content, increasing by a factor of 2.5 from 0.1 to 0.6 wt% and stabilizing from 0.6 to 1.4 wt%. The tracking of Pt species present under reaction conditions (230 °C, H2O/CO=4) was performed using operando DRIFT spectroscopy, CO-TPR and STEM in connection with the catalytic activity. A major structural change was found for Pt loadings above 0.6 wt% through the formation of metallic Pt0 nanoparticles of ca 1.4 nm from oxidized Pt single atoms and clusters. Conversely, for Pt contents below 0.6 wt%, Pt species possess a stronger interaction with CeO2 as well as a lower nuclearity, limiting their activation under reaction conditions. This strongly suggests that metallic Pt nanoparticles, prevalent at high loading, are more active than oxidic Pt single atoms and small clusters, which are predominantly present at low loading. This study highlights the key role of PtOx reducibility and the importance to optimize the Pt loading to obtain active catalysts for the water-gas shift reaction.